Prediction of air flow, methane, and coal dust dispersion in a room and pillar mining face - Yueze, L. (China University of Mining and Technology, 2017)
In underground coal mines, uncontrolled accumulation of methane and fine coal dust often leads to serious incidents such as explosion. Therefore, methane and dust dispersion in underground mines is closely monitored and strictly regulated. Accordingly, significant efforts have been devoted to study methane and dust dispersion in underground mines. In this study, methane emission and dust concentration are numerically investigated using a computational fluid dynamics (CFD) approach. Various possible scenarios of underground mine configurations are evaluated. The results indicate that the presence of continuous miner adversely affects the air flow and leads to increased methane and dust concentrations. Nevertheless, it is found that such negative effect can be minimized or even neutralized by operating the scrubber fan in suction mode. In addition, it was found that the combination of scrubber fan in suction mode and brattice results in the best performance in terms of methane and dust removal from the mining face. © 2017